Mucosal IgA Antibodies are Critical for Bacterial Clearance of Bordetella pertussis in the Baboon Model - Gaurav Chauhan; Melissa Gawron; Aaron Belli; Keith Reimann; Ryan Schneider; Yang Wang; Mark Klempner; Lisa Cavacini (Pathogens and Immunity)
Background: Despite the control of Bordetella pertussis with vaccine introduction, the incidence of pertussis has increased in the United States and globally. New vaccine strategies are clearly needed to regain control of this vaccine-preventable infection.